2011
DOI: 10.1177/0969733011408054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nurse educators’ and nursing students’ descriptions of teaching codes of ethics

Abstract: This study analysed teaching of nurses' codes of ethics in basic nursing education in Finland. A total of 183 educators and 214 students responded to a structured questionnaire. The data was analysed by SPSS. Teaching of nurses' codes was rather extensive. The nurse-patient relationship was highlighted. Educators assessed their teaching statistically significantly more extensive than what students' perceptions were. The use of teaching and evaluation methods was conventional, but differences between the groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…According to our findings, 57.4% and 40.0% of the nursing students revealed that they applied the codes in moderate and high levels, respectively. It was reported that the capability of nursing students in performing these codes were in moderate level (9). Moreover, 79% of the participants were fully agree or almost agree about the applicability of these codes (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to our findings, 57.4% and 40.0% of the nursing students revealed that they applied the codes in moderate and high levels, respectively. It was reported that the capability of nursing students in performing these codes were in moderate level (9). Moreover, 79% of the participants were fully agree or almost agree about the applicability of these codes (21).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to nursing codes of ethics that defines the profession (8), and are important in practice, hence, teaching codes of ethics during students studies are crucial, and can be effective in professionalization of nursing and development of professional values (9). In other words, decisionmaking in complicated ethical issues, professional values are the basis of nursing practice (10) Researchers believed that the main reason for inadequate knowledge on codes of ethics' in nurses was due to their limited education nursing curriculum (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, teaching on nurses' codes of conduct was rather extensive and highlighted the nurse-patient relationship. Educators assessed their teaching as statistically significantly more extensive than students perceived it as being (Numminen et al, 2011). Among health sciences faculty at two major Jordanian universities, most faculty members reported having no training in research ethics at their current institutions.…”
Section: Literature Reviewmentioning
confidence: 99%